Methodology Proposal, Virtual Simulations and 3D Printed Prototype of a Car Steering Wheel - Miriam Fandáková; Pavol Kudela; Maroš Jakubec; Eva Lieskovská (Applied Sciences)
The design and production of car steering wheel prototypes have evolved significantly with advancements in virtual and additive manufacturing technologies. This study presents a comprehensive methodology for the development of a car steering wheel prototype, integrating theoretical analysis, virtual simulations, and 3D printing. Initially, material characteristics are defined to ensure structural integrity and suitability for automotive use. Stress-strain simulations in a 3D virtual environment validate the mechanical feasibility and functional properties of the prototype. The methodology further includes criteria for selecting 3D printers based on material compatibility, build volume, and aesthetic requirements, such as color options. Finally, the study incorporates experimental testing of standardized samples, including compression and hardness tests, to verify the mechanical properties and deformation behavior under load. This integrated approach aims to streamline the prototype development process while ensuring precision, reliability, and customization.